The Temporal Dynamics of Neighborhood Disadvantage in Childhood and Subsequent Problem Behavior in Adolescence - Tom Kleinepier; Maarten van Ham (Institute of Labor Economics (IZA), 2018)
Research on neighborhood effects has increasingly focused on how long children have lived in a deprived neighborhood during childhood (duration), but has typically ignored when in childhood the exposure occurred (timing) and whether circumstances were improving or deteriorating (sequencing). Using Dutch register data, we applied sequence analysis to simultaneously capture duration, timing, and sequencing of exposure to neighborhood (dis)advantage in childhood. Compared to children who lived in a deprived neighborhood throughout childhood, we found that children who were exposed to neighborhood deprivation only during adolescence were equally likely to become a teenage parent and were more likely to drop out of school. Unexpectedly, children who lived in an affluent neighbor-hood throughout childhood were most likely to engage in delinquent behavior.
Keywords: I30; J60; P46; R23; 330; neighborhood effects; temporal dynamics; childhood; adolescence; problem behavior; sequence analysis